OP0106 SECUKINUMAB 150 MG SIGNIFICANTLY IMPROVED SIGNS AND SYMPTOMS OF NON-RADIOGRAPHIC AXIAL SPONDYLOARTHRITIS: 52-WEEK RESULTS FROM THE PHASE III PREVENT STUDY. (2nd June 2020) - Braun, J.; Blanco, R.; Dokoupilova, E.; Gensler, L. S.; Kivitz, A.; Hall, S.; Kameda, H.; Poddubnyy, D.; Van de Sande, M.; Van der Heijde, D.; Wiksten, A.; Porter, B.; et al.
Abstract : Background: Axial spondyloarthritis (axSpA) spectrum covers radiographic axSpA and non-radiographic axSpA (nr-axSpA). PREVENT (NCT02696031 ) is the first phase III, placebo (PBO) controlled study evaluating secukinumab (SEC) 150 mg with (LD) or without loading (NL) dose, in patients (pts) with nr-axSpA. 1 The study had 2 independent analysis plans as per EU (Wk 16) and US (Wk 52) regulatory requirements. Objectives: To report efficacy through Wk 52 and safety up to two years for the PREVENT study. Methods: 555 pts fulfilling ASAS criteria for axSpA plus abnormal CRP and/or MRI, without evidence of radiographic changes in sacroiliac (SI) joints according to modified New York Criteria for AS were enrolled. All images were assessed centrally before inclusion. Pts were randomised (1:1:1) to SEC 150 mg with LD, NL, or PBO at baseline (BL). LD pts received SEC 150 mg at Wks 1, 2, 3, and 4, and then every 4 wks (q4wk) starting at Wk 4. NL pts received SEC 150 mg at BL and PBO at Wks 1, 2, and 3, and then 150 mg q4wk. Switch to open-label (OL) SEC 150 mg or standard of care (SoC) was permitted after Wk 20. Primary endpoint was ASAS40 at Wk 16 (LD) and at Wk 52 (NL) in anti-TNF-naïve pts. Secondary endpoints (overall population) included ASAS40, BASDAI50, SI joint bone marrow edema (BME) score by MRI at Wks 16 and 52 and ASDAS-CRP inactive disease (ID) at Wk 52. Endpoints were analysed according to statistical hierarchy. Analysis used non responder imputation through Wk 52. Safety analyses included all pts who received ≥1 dose of study treatment. Results: Overall, 481 pts completed 52 wks with no major differences in retention across groups: 84.3% (156/185; LD), 89.7% (165/184; NL) and 86.0% (160/186; PBO). BL characteristics were similar across groups; 90% pts were anti-TNF-naïve, 56-58% pts had elevated CRP, 71-75% pts had evidence of SI joint inflammation by MRI. Proportion of pts who switched to OL or SoC between Wks 20 and 48 was 52.1% (LD), 49.2% (NL), and 67.4% (PBO). Primary endpoints at Wk 16 and Wk 52 were met (Table). SEC 150 mg LD or NL significantly improved secondary endpoints at Wk 16 and 52 vs PBO (Table). SEC significantly reduced SI joint MRI BME score vs PBO at Wk 16 (-1.68 and -1.03 vs -0.39; P = 0.0197 and 0.026, LD and NL respectively). No unexpected safety signals were reported. Conclusion: SEC 150 mg provided significant and sustained improvement in signs and symptoms of pts with nr-axSpA through Wk 52. MRI BME scores were reduced accordingly. There was no major difference between LD and NL. Safety of SEC was consistent with previous reports. 2 References: [1]Deodhar A, et al. Arthritis Rheumatol . 2019;71(suppl 10). [2]Deodhar A, et al . Arth Res Ther . 2019;21:111. Disclosure of Interests: Juergen Braun Grant/research support from: Abbvie (Abbott), Amgen, BMS, Boehringer, Celgene, Celltrion, Centocor, Chugai, Eli Lilly and Company, Medac, MSD (Schering Plough), Mundipharma, Novartis, Pfizer (Wyeth), Roche, Sanofi- Aventis, and UCB Pharma, Consultant of: Abbvie (Abbott), Amgen, BMS, Boehringer, Celgene, Celltrion, Centocor, Chugai, EBEWE Pharma, Eli Lilly and Company, Medac, MSD (Schering-Plough), Mundipharma, Novartis, Pfizer (Wyeth), Roche, Sanofi-Aventis, and UCB Pharma, Speakers bureau: Abbvie (Abbott), Amgen, BMS, Boehringer, Celgene, Celltrion, Centocor, Chugai, EBEWE Pharma, Eli Lilly and Company, Medac, MSD (Schering-Plough), Mundipharma, Novartis, Pfizer (Wyeth), Roche, Sanofi-Aventis, and UCB Pharma, Ricardo Blanco Grant/research support from: AbbVie, MSD, Roche, Consultant of: Abbvie, Eli Lilly, Pfizer, Roche, Bristol-Myers, Janssen, UCB Pharma and MSD, Speakers bureau: Abbvie, Eli Lilly, Pfizer, Roche, Bristol-Myers, Janssen, UCB Pharma. MSD, Eva Dokoupilova Grant/research support from: Eli Lilly, AbbVie, Novartis, Lianne S. Gensler Grant/research support from: Pfizer, Novartis, UCB, Consultant of: AbbVie, Eli Lilly, GSK, Novartis, UCB, Alan Kivitz Shareholder of: AbbVie, Amgen, Gilead, GSK, Pfizer Inc, Sanofi, Consultant of: AbbVie, Boehringer Ingelheim, Flexion, Genzyme, Gilead, Janssen, Novartis, Pfizer Inc, Regeneron, Sanofi, SUN Pharma Advanced Research, UCB, Paid instructor for: Celgene, Genzyme, Horizon, Merck, Novartis, Pfizer, Regeneron, Sanofi, Speakers bureau: AbbVie, Celgene, Flexion, Genzyme, Horizon, Merck, Novartis, Pfizer Inc, Regeneron, Sanofi, Stephen Hall Grant/research support from: Abbvie, UCB, Janssen, Merck, Hideto Kameda Grant/research support from: Abbvie, Asahi-Kasei, Chugai, Eisai, Mitsubishi-Tanabe and Novartis, Consultant of: Abbvie, Boehringer, Celgene, Eli Lilly, Janssen, Novartis, Sanofi, UCB, Speakers bureau: Abbvie, Asahi-Kasei, BMS, Chugai, Eisai, Eli Lilly, Janssen, Mitsubishi-Tanabe, Novartis and Pfizer, Denis Poddubnyy Grant/research support from: AbbVie, MSD, Novartis, and Pfizer, Consultant of: AbbVie, Bristol-Myers Squibb, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB, Marleen van de Sande Grant/research support from: Novartis, Eli Lilly, Boehringer Ingelheim, Janssen, Consultant of: Abbvie, Novartis, Eli Lilly, Speakers bureau: Novartis, MSD, Désirée van der Heijde Consultant of: AbbVie, Amgen, Astellas, AstraZeneca, BMS, Boehringer Ingelheim, Celgene, Cyxone, Daiichi, Eisai, Eli-Lilly, Galapagos, Gilead Sciences, Inc., Glaxo-Smith-Kline, Janssen, Merck, Novartis, Pfizer, Regeneron, Roche, Sanofi, Takeda, UCB Pharma; Director of Imaging Rheumatology BV, Anna Wiksten Shareholder of: Novartis, Employee of: Novartis, Brian Porter Shareholder of: Novartis, Employee of: Novartis, Hanno Richards Shareholder of: Novartis, Employee of: Novartis, Sibylle Haemmerle Shareholder of: Novartis, Employee of: Novartis, Atul Deodhar Grant/research support from: AbbVie, Eli Lilly, GSK, Novartis, Pfizer, UCB, Consultant of: AbbVie, Amgen, Boehringer Ingelheim, Bristol Myer Squibb (BMS), Eli Lilly, GSK, Janssen, Novartis, Pfizer, UCB, Speakers bureau: AbbVie, Amgen, Boehringer Ingelheim, Bristol Myer Squibb (BMS), Eli Lilly, GSK, Janssen, Novartis, Pfizer, UCB